2016
DOI: 10.1007/s13277-016-5235-3
|View full text |Cite
|
Sign up to set email alerts
|

TCF-1 participates in the occurrence of dedifferentiated chondrosarcoma

Abstract: The present study demonstrated that T cell factor 1 (TCF-1) protein, a component of the canonical Wnt/β-catenin signaling pathway, can regulate the expression of runt-related transcription factor 2 (runx2) gene and Sry-related HMG box 9 (sox9) gene, which may participate in the differentiation of chondrosarcoma. Dedifferentiated chondrosarcoma (DDCS) is a special variant of conventional chondrosarcoma (CCS), associated with poor survival and high metastasis rate. However, little is known about the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…TCF-1 has been involved in bone formation (38), thermogenesis by brown adipocytes (39), pancreatic β-cell survival and glucose tolerance (40), although the cells in which TCF-1 is expressed are not well defined. Finally, aberrant expression and function of TCF-1 is associated with various diseases, and many cancers (41)(42)(43)(44)(45). Understanding the mechanisms by which TCF1 is regulated in these various cell type could enable us to target TCF-1 expression in specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…TCF-1 has been involved in bone formation (38), thermogenesis by brown adipocytes (39), pancreatic β-cell survival and glucose tolerance (40), although the cells in which TCF-1 is expressed are not well defined. Finally, aberrant expression and function of TCF-1 is associated with various diseases, and many cancers (41)(42)(43)(44)(45). Understanding the mechanisms by which TCF1 is regulated in these various cell type could enable us to target TCF-1 expression in specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The LEF/TCF family members are the primary binding complex of the Wnt/β-catenin signaling pathway, which regulates a variety of oncogenic genes, such as c-Myc, Cyclin D1, and Runx2 (Li et al, 2013;Liang et al, 2018;McQueen et al, 2011). Different LEFs/TCFs regulate their target genes in different ways (Hrckulak, Kolar, Strnad, & Korinek, 2016); for instance, TCF-1 and LEF-1 act as transactional Emerging evidence suggests that TCF-1 plays a role in cancers, including chondrosarcoma (Xu et al, 2016). Our results also demonstrated that TCF-1 is overexpressed in OS and is required for its survival.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, HSP90 depletion suppressed both the expression of β-catenin and TCF-1 (Figure 3b,c). Because activation of Wnt/β-catenin signaling can be regulated by HSP90 in OS and TCF-1 is essential for β-catenin/TCF-1 complex formation (Liang et al, 2018;Okayama et al, 2014;Xu et al, 2016), we next examined whether the downregulation of TCF-1 involves β-catenin. As shown in Figure 3d, knockdown of β-catenin by siβ-c#3 (siβ-catenin#3) and siβ-c#4 (siβ-catenin#4) further depleted the expression of TCF-1 and Cyclin D1 in Saos-2 cells, indicating that the basal level of β-catenin is required for HSP90-regulated TCF-1 expression.…”
Section: Hsp90 Regulates Tcf-1 Expression At the Transcriptional And Proteasomal Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…TCF7 can recognize and bind to the DNA sequence called Wnt response element (WRE) through the HMG domain, cause conformational changes of DNA and chromatin that lead to further binding of other transcription complexes ( 19 ), and promote the expression of Wnt target genes ( 20 ). Previous studies have shown that TCF7 is closely related to the development and progression of various malignancies, such as leukemia ( 21 ), chondrosarcoma ( 22 ), and prostate cancer ( 23 , 24 ). In colorectal tumors, the transcription of Wnt target genes mediated by TCF7 is necessary for the initial activity of tumor stem cells ( 25 ).…”
Section: Introductionmentioning
confidence: 99%